Estrategias de nutrición con soluciones enraizantes más bioestimulantes en plántulas de chirimoya (Annona cherimola Mill.) y su efecto sobre el crecimiento inicial - Herrera Morocho, Wendy Salomé (2024)
Cherimoya cultivation, part of the Annonaceae family, originates in Central America. In Ecuador, the main production areas are located in the provinces of Imbabura, Pichincha, Tungurahua, Azuay, and Loja. Despite its significant potential, cherimoya cultivation has not been widely studied, particularly in terms of plant nutrition, which is crucial for its growth and development. This research aimed to proposed nutritional strategies using rooting solutions combined with bio stimulants in cherimoya seedlings and to evaluate their effect on early growth. The study conducted at the La Argelia Experimental Farm in the province of Loja, using a completely randomized block design (CRBD) with a bifactorial arrangement (A*B). Factor A represented the rooting solutions (Raizal 400 and DAP), while factor B included the bio stimulants (Evergreen, Alga-Q, and Humus 12.5%). The experiment consisted of 12 treatments with 5 replications each, with each experimental unit comprising a group of 20 seedlings, in total 1,200 seedlings. The results showed that the combinations of both factors significantly improved vegetative growth variables, such as stem diameter (average of 0.64 cm), leaf area (average of 79.71 cm2), plant cover (39.44%) and chlorophyll content (45.50 SPAD units). The best results were achieved with the Raizal plus Alga-Q treatment. In terms of plant height, Raizal had the greatest effect, with an average height of 28 cm. Additionally, the application of DAP significantly increased the electrical conductivity and pH of the substrate, leading to higher salt content. Regarding the number of leaves, Alga-Q had a notable impact, producing an average of 14 leaves per plant.